Rebuilding Harmony: Social Interactions After the Maluku Conflict - Wenno, Yulian Hermanus; Pelu, Nadya Asalan; Hutagalung, Elisa; Karim, Osama; Samen, Fatma (Guidance and Counseling Study Program, Pattimura University, 2024)
The purpose of this study was to determine the dynamics of social interactions that were passed down from previous generations in students of the BK Study Program after the Maluku conflict. The research method used a qualitative approach with in-depth interviews with students whose families experienced the conflict in Maluku directly in 1999-2002. Through coding analysis, the research identified thematic patterns and meanings that emerged from students' narratives. Based on the results of the study, it was found that the social interaction of post-conflict Counseling students both individually and in groups can be established with active communication between students of different religions with tolerance as an attitude to maintain harmony in social relations during the study period and emphasize the need for integration of social aspects reflected in the study program curriculum so that the unique experience of each post-conflict student passed down from generation to generation can adapt to the campus environment commonly dubbed the